Management of chronic kidney disease in type 2 diabetes: screening, diagnosis and treatment goals, and recommendations. Issue 4 (19th May 2022) - Shubrook, Jay H.; Neumiller, Joshua J.; Wright, Eugene
ABSTRACT: Patients with chronic kidney disease (CKD) and type 2 diabetes (T2D) are at high risk of CKD progression and cardiovascular (CV) disease. Prevalence of CKD in patients with T2D is currently around 40% and continues to grow. The increasing number of people with CKD and T2D will ultimately have a significant impact upon health resource use and costs of care for people with T2D. Management of CKD in patients with T2D aims to preserve kidney function to reduce the risk of end-stage kidney disease, CV events, and mortality. Evidence-based recommendations for the treatment of patients with CKD and T2D are provided by several international and national organizations and recommend several lifestyle and pharmacological approaches to help prevent or delay the progression of CKD in patients with T2D. Guidelines include regular screening of patients with T2D for CKD using spot urine albumin-to-creatinine ratio (UACR) and estimated glomerular filtration rate (at least annually and at least twice a year if UACR >300 mg/g). Additionally, assessment of vascular complications, together with interventions designed to improve glycemic control and lipid levels, maintain healthy body weight, and optimize blood pressure should be performed. Medications shown to slow progression of CKD include renin–angiotensin system inhibitors, sodium-glucose cotransporter-2 inhibitors, glucagon-like peptide 1 receptor agonists, and, more recently, selective, non-steroidal mineralocorticoid receptor antagonists. This review highlights the ongoing challenges facing primary care providers in the management of CKD in patients with T2D including the consideration of comorbidities, adoption of new treatment options, and implementation of individualized care. Achieving consensus for optimal treatment of this disease is critical in providing consistent and appropriate care for all patients. Strategies to improve outcomes should also include use of clear referral criteria, use of a multi-disciplinary approach, and patient education.